Reading or translating words in story contexts facilitates their production the next day: Evidence from bilingual repetition priming. - Francis, Wendy S.; Guedea Morales, Erika L.; Gurrola, Bianca V. (Memory & Cognition, 2025)
Everyday language experience increases the efficiency of word production. The possible link between this type of learning and the memory phenomenon of repetition priming was explored in a bilingual repetition-priming experiment. Spanish–English bilinguals read or translated short stories containing target words that corresponded to pictures to be named at test, with retention intervals of several minutes or at least 24 h. Repetition priming in picture-naming RTs was significant following story translation in either direction or story reading in the language of the picture-naming test. These effects persisted across a retention interval of at least 24 h, indicating that the speeded word production reflects long-term learning. Thus, practice with either comprehension or production of contextualized words elicits long-term benefits for later production. In contrast to previous studies with isolated words or words embedded in short sentences, the priming effects in picture-naming RTs did not differ across encoding conditions. This pattern suggests that in complex language contexts, the comprehension processes of reading and translation are similar and the top-down processes elicited by comprehension and production practice are similarly beneficial in speeding later production. However, it remains a challenge to explain patterns of repetition-priming effects in accuracy, which represent enhanced probability of access to word forms that are not reliably produced.